1990
DOI: 10.1212/wnl.40.6.966
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the basal temporal language area in patients with left temporal lobe epilepsy

Abstract: We evaluated 5 consecutive patients with subdural grid electrodes (including placement over the left basal temporal region) for focal resections for control of intractable epilepsy. All 5 had language dysfunction when we performed cortical stimulation over the basal temporal region (the inferior temporal gyrus, the parahippocampal gyrus) using a systematic battery of language tests. The area in which language interference could be produced began from at least 11 to 35 mm posterior to the temporal tip and ended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 0 publications
9
77
1
Order By: Relevance
“…the epileptogenic zone at the anterior temporobasal cortex and two patients with left-sided temporal lesions eventually became seizure-free after surgery demonstrates that ictal aphasia can primarily originate in this brain area, instead of spreading from primary language areas (e.g., Wernicke's and Broca's areas). Supporting this observation, electrocortical stimulation of the BTLA, the area where the lesions described in this series were located, produces a wide range of speech manifestations in patients with epilepsy similar to that observed in our patients with left-sided lesions [1][2][3], The paucity of literature regarding our observations may be explained by several reasons. Firstly, when language is impaired during a seizure, assessing level of awareness is difficult, and alteration of consciousness is assumed in most cases.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…the epileptogenic zone at the anterior temporobasal cortex and two patients with left-sided temporal lesions eventually became seizure-free after surgery demonstrates that ictal aphasia can primarily originate in this brain area, instead of spreading from primary language areas (e.g., Wernicke's and Broca's areas). Supporting this observation, electrocortical stimulation of the BTLA, the area where the lesions described in this series were located, produces a wide range of speech manifestations in patients with epilepsy similar to that observed in our patients with left-sided lesions [1][2][3], The paucity of literature regarding our observations may be explained by several reasons. Firstly, when language is impaired during a seizure, assessing level of awareness is difficult, and alteration of consciousness is assumed in most cases.…”
Section: Discussionsupporting
confidence: 87%
“…However, accumulating evidence suggests that the temporal pole and the temporal basal area play an important functional role in the language system, which could account for specific features of seizures arising here. Electrophysiological studies demonstrated that surface electrical stimulation during epilepsy surgery of a basal temporal language area (BTLA) produces a range of speech disturbances [1][2][3]. A combination of neuroimaging and neuropsychological studies has subsequently improved our understanding of the functional role of these dominant anterior temporal lobe areas in language [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Picture-naming stimuli were 35 line drawings from the Boston Naming Test. Reading stimuli were 50 single words of three to seven letters that patients read aloud (Burnstine et al, 1990). Auditory comprehension was assessed with 30 one-step verbal directions from the Token Test.…”
Section: Electrocortical Stimulation Mappingmentioning
confidence: 99%
“…Baseline auditory discrimination testing was used for statistical comparisons with patients' ESM performances. Baseline language testing identified for exclusion stimuli that elicited incorrect responses, ensuring accurate response scoring during clinical ESM (Burnstine et al, 1990;Boatman et al, 2000). An ESM nurse and technician, blinded to patients' group status, performed the baseline testing and ESM studies under supervision of an epileptologist.…”
Section: Electrocortical Stimulation Mappingmentioning
confidence: 99%
“…12) The basal temporal regions induce certain language dysfunction using a systematic battery of language tests. 1) Especially in transcription and mental recall tasks of Japanese`kanji' morphograms, functional MR imaging showed lateralized activation of the basal temporal regions including the left posterior ITC. In contrast, neither oral reading nor semantic judgment produced similar activation of this area.…”
Section: Discussionmentioning
confidence: 99%